Editor’s Highlight: Pulmonary Vascular Thrombosis in Rats Exposed to Inhaled Sulfur Mustard - McGraw, Matthew D. (Toxicol Sci, 2017)
Sulfur mustard (SM) is a chemical warfare agent. When inhaled, SM causes significant injury to the respiratory tract. Although the mechanism involved in acute airway injury after SM inhalation has been well described previously, the mechanism of SM’s contribution to distal lung vascular injury is not well understood. We hypothesized that acute inhalation of vaporized SM causes activated systemic coagulation with subsequent pulmonary vascular thrombi formation after SM inhalation exposure. Sprague Dawley rats inhaled SM ethanolic vapor (3.8 mg/kg). Barium/gelatin CT pulmonary angiograms were performed to assess for pulmonary vascular thrombi burden. Lung immunohistochemistry was performed for common procoagulant markers including fibrin(ogen), von Willebrand factor, and CD42d in control and SM-exposed lungs. Additionally, systemic levels of d-dimer and platelet aggregometry after adenosine diphosphate- and thrombin-stimulation were measured in plasma after SM exposure. In SM-exposed lungs, chest CT angiography demonstrated a significant decrease in the distal pulmonary vessel density assessed at 6 h postexposure. Immunohistochemistry also demonstrated increased intravascular fibrin(ogen), vascular von Willebrand factor, and platelet CD42d in the distal pulmonary vessels (<200 µm diameter). Circulating d-dimer levels were significantly increased (p < .001) at 6, 9, and 12 h after SM inhalation versus controls. Platelet aggregation was also increased in both adenosine diphosphate - (p < .01) and thrombin- (p < .001) stimulated platelet-rich plasma after SM inhalation. Significant pulmonary vascular thrombi formation was evident in distal pulmonary arterioles following SM inhalation in rats assessed by CT angiography and immunohistochemistry. Enhanced systemic platelet aggregation and activated systemic coagulation with subsequent thrombi formation likely contributed to pulmonary vessel occlusion.